Incidence of financial education in the improvement of the Production Costs of the Inclusive Rural Businesses of the Haku Wiñay / Nao Jayatai Project PP - 0118 "Access of rural households with subsistence economy to local markets - Núcleo Ejecutor Central - Wong Copaja, Edgard Enrique (2020)
This study determines the incidence that financial education has on the production costs of the inclusive rural businesses of the Haku Wiñay project, the Haku Wiñay project is a project to develop productive capacities and entrepreneurship, to increase and diversify autonomous income sustainable, in households in a situation of poverty and extreme poverty, located in the rural populated centers of the coast, mountains and jungle of Peru. "Haku Wiñay" and in Shipibo-conibo "Noa Jayatai" means "We are going to grow" The type of research is pure, since it is aimed at achieving new knowledge aimed at seeking solutions to practical problems through the impact of financial education on the production costs of rural businesses. The research design is descriptive since it will be measured in a certain time, as the researcher's interference in the study is observational, the period that the information is captured is prospective, the development of the topic studied is cross-sectional and the number of population studied is descriptive. Said evaluation was carried out by means of a survey designed and validated by the judgment of experts, obtaining 95% acceptance of viability. Similarly, the Cronbach Alpha test was carried out, obtaining 0.988, which makes it a reliable instrument and ensures certainty. From the results. It was applied to a sample of seventy (70) users of the project who have their ventures in the palca and pachia area of ??the Tacna region.